Investigation of an HD Engine Thermal Storage System. (May 2017) - Li, Jun; Tam, Chin Hong; Tian, Guohong
Abstract: This paper presents a theoretical calculation and a preliminary design of a thermal storage system (TSS) for a heavy duty diesel engine, in order to re-utilise the wasted heat from the engine when in operation and reduce the warm-up time, thus reducing the engine emissions and improve the performance. The thermal storage mainly comprises of a heat exchanger filled with phase change material. A group of candidate materials were evaluated and NaOH H2 O was selected for the particular application, as its phase change temperature is suitable and latent heat is relatively high. The storage was preliminarily designed considering the size of the engine and the quantity of heat requested, and the improvement of the engine was evaluated. The theoretical calculation suggested that nearly 40% improvement in warm-up time could be achieved with the TSS.